Safety and Feasibility of Carboplatin and Paclitaxel followed by Fluoropyrimidine Analogs and Radiation as Adjuvant Therapy for Gastric Cancer - Mohammad Mobayed; Lance K. Heilbrun; Anthony F. Shields; Tara Washington; Raghu Venkatramanamoorthy; Philip A. Philip; Bassel F. El-Rayes (Case Reports in Oncology, 2009)
Background: Adjuvant 5-fluorouracil (5FU)-based chemo-radiotherapy is currently considered a standard of care for the treatment of gastric cancer. The impact of 5FU-based adjuvant therapy on the rate of distant recurrence has been modest. In order to improve the systemic effects of adjuvant therapy, we have been treating patients with resected gastric cancer with carboplatin and paclitaxel followed by fluoropyrimidine analogue and radiation. Methods: We report on the outcomes of 21 consecutive gastric cancer patients treated off protocol with adjuvant carboplatin (area under the curve 5 mg/ml × min) and paclitaxel (175–200 mg/m2) every 3 weeks, followed by concurrent pyrimidine analogs (either capecitabine 1,600–2,000 mg/m2/day in 17 patients, or 5FU 200 mg/m2/day in 4 patients) and radiation (45–50.4 Gy). Patients received a total of 4–6 cycles of carboplatin and paclitaxel. Results: The median age at diagnosis was 60 years. Sixteen patients had stage 3 disease and 7 of them had positive surgical margins (6 with R1 and 1 with R2 resection), 3 patients were stage 2, and 2 patients were stage 1 (all had R0 resection). All patients had D1/D2 (4 had D2 and 17 had D1) lymph node dissection. The incidence of grade 3 or higher overall, hematologic, or gastrointestinal toxicity in the patients receiving carboplatin and paclitaxel was 57, 48 and 10%, respectively. No treatment-related deaths were observed. After adjuvant treatment 15 patients developed recurrent disease, 10 of whom had distant metastases. The median recurrence-free survival (RFS) was 12.3 months. The median overall survival (OS) was 16.0 months. Patients with R0 resection had significantly longer OS than did those with positive surgical margins (log-rank p = 0.0060). Median OS for the R0 resection group was 28.8 months. Conclusions: Carboplatin and paclitaxel added to radiation plus fluoropyrimidine analogs is a well-tolerated regimen in the adjuvant setting. The activity of this regimen in this relatively high-risk group of gastric cancer patients is of interest for future development.